Setting Up Treasuries in the Baltics, Russia, and other Countries of the Former Soviet Union - Diamond, Jack (Occasional Papers; Occasional Paper ;, 2000)
This paper reviews lessons learned for future technical assistance work in the hope that they will highlight the problems faced when introducing institutional changes in transitional economies. The findings from the assessment are intended principally for those interested in the development of these transition economies, but should also be of wider relevance to those involved in delivering technical assistance on public sector institutional reform. The assessment follows the standard approach to such evaluation work. It first considers whether the basic goal of setting up treasuries has been achieved and whether the resultant reforms are relevant and sustainable. A more marked improvement in public expenditure and fiscal management was, however, also seriously hindered by the hostile macroeconomic environment of perennial crisis. The IMF is now preparing an illustrative standard for budget preparation, based on the Code of Good Practices on Fiscal Transparency, for the countries discussed in this paper.